Well-being, familial risk, and transfusion interval in thalassemia-affected families: A two-step cluster analysis - Arulmani Thiyagarajan; M Bhagvandas; Kalpana Kosalram; Sudip Bhattacharya (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Thalassemia is an inherited blood disorder which is one of the common genetic disorders among children that is increasing worldwide. AIM AND OBJECTIVE: This study aimed to identify clustering patterns among thalassemia-affected families based on their well-being, transfusion interval, and risk factors using two-step cluster analysis (TCA). METHODS: The study design is a descriptive, analytical cross-sectional study. The study sample consisted of 125 thalassemia children along with either one of the parents who referred to a thalassemia treatment center of a pediatric hospital in Chennai, Tamil Nadu. The parents and children were evaluated using the Ryff Psychological Well-being Scale and Kidscreen Questionnaire respectively. Data were analyzed using SPSS version 16.0 software. RESULTS: Out of 125 parents, 86 were father (68.8%) and 39 were mother (31.2%). The mean age of parents was 38 years. Similarly, out of 125 thalassemia-affected children, the mean age of children was 13 years. Six clusters were deducted from the TCA. Parents' well-being variable does not have discriminating power to form cluster division. Three cluster formations were meaningful. CONCLUSION: TCA, in this study, helps in finding the clusters of families with thalassemia-affected children associated with poor well-being and familial risks, which require attention for medical counseling.